Comportamiento agronómico y valoración nutricional de Kudzu tropical (Pueraria phaseloides) y clitoria (Clitoria ternatea) - Ludeña Macías, Carlos Ovidio (2011)
In the property "María" of the Technical State University of the canton Quevedo, county of Ríos was determined the agronomic "Behavior and nutritional value of tropical (Pueraria phaseloides) Kudzú and Clitoria (Clitoria ternatea)" in different states of maturity, where they took as objectives to analyze the agronomic behavior of two varieties of leguminous and to carry out the analyses bromatológicos to determine the nutritional value, using a design of complete blocks at random (DCA). In the simple effect of the leguminous ones, leguminous Clitoria obtained the best indexes in the variables root (37,53 g) weight, forage (40,12 g) weight, weight of leaves (14,10 g) and shaft (16,00 g) weight. And the best relationship hoja:tallo and it leaves aérea:parte radicular he/she showed up in leguminous Clitoria with 0,84 and 1,04. In the simple effect of the ages the highest results in the variables forage weight, weight of leaves and relationship hoja:tallo corresponded to the age of 80 days. The best index for the variable relationship leaves aérea:parte radicular it was shown in the age of 110 days and the best root weight and relationship leaves aérea:parte radicular it was reported to the 140 days of age. In the interaction of the varieties of leguminous for the ages, the biggest root (37,50kg) weight showed up in Clitoria to the 110 days, in a same way to the 80 days, the best forage (78,05 kg) weight, weight of leaves (27,15 kg) and weight of shafts (22,55 kg) also registered in the same one leguminous. The best relationship hoja:tallo and it leaves aérea:parte radicular to the 110 days it was respectively in leguminous Kudzú with 1,57 and 2,93. The protein greater levels were obtained with leguminous Clitoria to the 80, 110 and 140 days with 19,50; 16,25 and 13,82%. For the composition microbiológica, the tall populations in bacterias (9,5 x 105), actinomicetos (8,3 x 106) to the 80 days, and fixers of N asimbiótico (3,4 x 10 3) to the 140 days showed up with Clitoria. The tall populations for mushrooms (5,0 x 104) and solubilizadores of P (4,6 x 104) were reported in Kudzú to the 80 days. The bigger than colonization (65,53%) percentage showed up in Kudzú to the 140 days, and the biggest endófitos density with Clitoria to the same age with 2,60%. For the obtained results you confirmed the outlined hypothesis: "The nutritious value of leguminous Clitoria (Clitoria ternatea) for the three court ages will be superior" and the hypothesis was discarded: "Tropical (Pueraria phaseloides) leguminous Kudzú will show the biggest production of biomass in the different states of maturity."